Derivation of Stem Cell-like Cells From Spherical Culture of Astrocytes for Enhanced Neural Repair After Middle Cerebral Artery Occlusion - Zhu, Dan; Cao, Zheming; Pang, Xiaoyang; Jiang, Wei; Li, Chihao; Zhang, Xing; Tian, Xibin; Tu, Haijun; Wu, Panfeng; Nie, Hemin (Frontiers in Bioengineering and Biotechnology, 2022)
Neural precursor cells (NPCs) tend to aggregate and develop into three-dimensional (3D) spheres, which in turn help maintain the stemness of the cells. This close relationship between spherical environments and cell stemness direct us to assume that 3D spheres of astrocytes (ASTs) may facilitate the acquisition of stem cell-like features and generate sufficient seed cells for the regeneration of neurons. In vitro results confirmed that mouse ASTs cultured on agarose surfaces spontaneously formed cell spheres and exhibited molecular features similar to stem cells, particularly capable of further differentiating into neurons and forming functional synaptic networks with synchronous burst activities. RNA-sequencing results revealed the similarity between AST-derived stem cells (A-iSCs) and NPCs in global gene expression profiles. The potency of A-iSCs in repairing neural injuries was evaluated in a mouse model of middle cerebral artery occlusion. It was observed that the transplanted A-iSCs expressed a series of markers related to neural differentiation, such as NeuN, Tuj1, and Map2, indicating the conversion of the transplanted A-iSCs into neurons in the scenario. We also found that the injured mice injected with A-iSCs exhibited significant improvements in sensorimotor functions after 8 weeks compared with the sham and control mice. Taken together, mouse ASTs form cell spheres on agarose surfaces and acquire stem cell-associated features; meanwhile, the derived A-iSCs possess the capacity to differentiate into neurons and facilitate the regeneration of damaged nerves.